2008
DOI: 10.1007/s10811-008-9375-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zostera detritus as a potential new source of zosteric acid

Abstract: Detritus of the seagrasses Zostera noltii and Z. marina collected on the beaches of Arcachon Lagoon (France) over a 3-year period was screened as a new source of zosteric acid (ZA). This natural sulphated phenolic acid is a high value-added product capable of preventing settlement of marine organisms and protecting crops from fungal diseases. The seasonal variation of the ZA content was quantified in methanolic and aqueous crude extracts using high-performance liquid chromatography. The concentration found ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…Similarly, zosteric acid (ZA), chemically p-(sulfooxy) cinnamic acid, becomes noteworthy for its anti-fouling activity 29 , which has been proved to inhibit the growth of biofilm forming bacteria 30,31 and fungal spores 32 . Both the living leaves 33 and the detritus of the seagrasses Z. noltii and Z. marina serve as a rich source of ZA that could justify significant exploitation of this low cost, very abundant and renewable, but relatively unused, marine resource 34 . Chemical structures of the phenolic compounds from seagrasses are presented in Figure 3.…”
Section: Phenylmethane and Phenylethane Derivativesmentioning
confidence: 99%
“…Similarly, zosteric acid (ZA), chemically p-(sulfooxy) cinnamic acid, becomes noteworthy for its anti-fouling activity 29 , which has been proved to inhibit the growth of biofilm forming bacteria 30,31 and fungal spores 32 . Both the living leaves 33 and the detritus of the seagrasses Z. noltii and Z. marina serve as a rich source of ZA that could justify significant exploitation of this low cost, very abundant and renewable, but relatively unused, marine resource 34 . Chemical structures of the phenolic compounds from seagrasses are presented in Figure 3.…”
Section: Phenylmethane and Phenylethane Derivativesmentioning
confidence: 99%
“…The aqueous phase was retained and washed by addition of methanol and finally the desired product with a yield of 52% was obtained. [8,10,16,17] 2.5 Loading of the Biocide into the Porous Material of the Zeolite (ZSM-5)…”
Section: Synthesis Of Biocide (Zosteric Acid)mentioning
confidence: 99%
“…7, it can be clearly seen that the polarization response of the coating system '1' namely (biocide loaded Zeolite modified epoxy coating) 30 days of immersion was towards the anodic side, indicating their superior corrosion resistance than the response of coating system '2'. This superior corrosion resistance offered by coating system '1' might be due to the molecular structure of the biocide (Zosteric acid) [10,17], which was able to adsorb on the metal surface through the π-electrons of the aromatic ring and lone pair of electrons of the sulphur atom [20]. A similar observation was made by Zhongyi He et al [21,24] who further explained the relationship between molecular structures and revealed that the corrosion behaviour properties improve with increasing number of the electronegative atoms, thereby increasing the co-ordination capacity of the heterocyclic molecules that influence the stability and protective properties of the cured film [22].…”
Section: Effect Of Biocide (Zosteric Acid) On the Epoxy Coatingsmentioning
confidence: 99%
“…L-Chiro-inositol was isolated from Syringodium filliforme [18]. Detritus of seagrasses Zostera noltii and Zostera marina was screened as a new source of zosteric acid [19] and rosmarinic acid [20]. Syphonosid was isolated from Halophila stipulacea [21].…”
Section: Introductionmentioning
confidence: 99%